Validation of geotechnical laboratory tests data obtained from various sources - Veronika Pavelcová; Tomáš Janda (Acta Polytechnica CTU Proceedings)
Data validation is a critical step in every data analysis. It is a well-known fact that the results of any data analysis are directly dependent on the input values. This paper works with a worldwide database of laboratory tests collected during four year operation of web calibration application ExCalibre and elaborates on the data correctness. ExCalibre application enables automatic calibration of three critical state models based on data from standard laboratory tests. The paper presents the rules and overall methodology for checking the validity of laboratory tests data and summarises the obtained results.